Chemical composition, antibacterial, anticancer, and anti-a-glucosidase activities of essential oils from Alpinia nelumboides - Van Thi Kieu Tran, Thang Truong Le, Chuong Hoang Nguyen, Thao Nguyen Thi Tran, Viet Hoang (Journal of Applied Pharmaceutical Science, 2024)
The chemical composition and biological properties of essential oils extracted from the rhizomes and leaves of Alpinia nelumboides were examined in this study. The oils were isolated via hydrodistillation using a Clevenger apparatus and analyzed with GC-FID/MS. Antibacterial activity against antibiotic-resistant bacterial strains was evaluated using the agar microdilution method. Anticancer and α-glucosidase inhibitory activities were assessed through in vitro assays. Eucalyptol was identified as the major component, accounting for 71.23% and 32.82% of the rhizome and leaves oils, respectively. Both rhizome and leaf extracts exhibited antibacterial activity against several antibiotic-resistant bacterial strains, with minimum inhibitory concentration values ranging from 8 to 16 mg/ ml. The rhizome essential oil demonstrated anticancer properties against NCI-H460 (IC50 = 98.28 ± 5.22 μg/ml) and HepG2 (IC50 = 189.87 ± 3.16 μg/ml) cell lines. Additionally, it showed α-glucosidase inhibitory activity (IC50 = 2.42 mg/ml). The essential oils obtained from A. nelumboides possess promising biological activities, including antibacterial, anticancer, and α-glucosidase inhibitory properties. These findings suggest their potential use as healthcare pharmaceuticals in the future.
Keywords: Alpinia nelumboides, Zingiberaceae, chemical composition, biological activities, essential oils